Injuries at the Konica 1997 Asian Judo Championships - Pieter, W.; Talbot, C.; Pinlac, V.; Bercades, L. T. (2001)
The purpose of this study was to assess the injury profile in Asian elite judo athletes. Subjects were male (n=100) and female (n=84) elite judoka participating in the Konica 1997 Asian Judo Championships in Metro Manila, Philippines. Injury data were collected with simple check-off forms that describe the athlete, type, location and mechanism of injury. An injury was defined as any circumstance for which assistance was sought from the medical personnel. The Mann-Whitney U test was used to determine the difference in total injury rate between males and females. The women recorded a higher total injury rate (41.28/1,000 athlete-exposures) than the men (25.18/1,000 athlete-exposures) (p<0.001). The major injury type was the abrasion (13.76/1,000 athlete-exposures) in the women, while no one injury type was dominant in the men. The body part most often injured in the women was the toes (9.17/1,000 athlete-exposures) and in the men, the wrist (10.79/1,000 athlete-exposures). Although the sample was too small to arrive at any definitive inferences, the Asian judoka in the present study incurred most of the injuries to the upper extremities (10.79/1,000 athlete-exposures for the men and 18.35/1,000 athlete-exposures for the women). The major injury mechanism in the women was groundwork (13.76/1,000 athlete-exposures) and in the men, executing a throw (7.19/1,000 athlete-exposures). The total injury rates of the Asian judoka compare favorably to those of their western counterparts.